PiggyBac Transposon-Mediated Transgenesis in the Pacific Oyster (Crassostrea gigas) – First Time in Mollusks - Chen, Jun; Wu, Changlu; Zhang, Baolu; Cai, Zhongqiang; Wei, Lei; Li, Zhuang; Li, Guangbin; Guo, Ting; Li, Yongchuan; Guo, Wen; Wang, Xiaotong (Frontiers in Physiology, 2018)
As an effective method of transgenesis, the PiggyBac transposon system has been widely used in various organisms but not yet in mollusks. In this work, piggyBac containing green fluorescent protein (GFP) was transferred into the Pacific oyster (C. gigas) by sperm-mediated gene transfer with or without electroporation. Fluorescent larvae were then observed and isolated under an inverted fluorescence microscope, and insertion of piggyBac was tested by PCR using genomic DNA as template. Oyster larvae with green fluorescence were observed after transgenesis with or without electroporation, but electroporation increased the efficiency of sperm-mediated transgenesis. Subsequently, piggyBac-gGH containing GFP and a growth hormone gene from orange-spotted grouper (gGH) was transferred into oysters using sperm mediation with electroporation, and fluorescent larvae were observed and isolated. The insertion of piggyBac-gGH was tested by PCR and genome walking analysis. PCR analysis indicated that piggyBac-gGH was transferred into oyster larvae; genome walking analysis further showed the detailed location where piggyBac-gGH was inserted in the oyster genome. This is the first time that piggyBac transposon-mediated transgenesis has been applied in mollusks.